Cytomegalovirus Infection Impairs Immunosuppressive and Antimicrobial Effector Functions of Human Multipotent Mesenchymal Stromal Cells. (23rd March 2014) - Meisel, Roland; Heseler, Kathrin; Nau, Julia; Schmidt, Silvia Kathrin; Leineweber, Margret; Pudelko, Sabine; Wenning, Johannes; Zimmermann, Albert; Hengel, Hartmut; Sinzger, Christian; Degistirici, Özer; Volker Sorg, Rüdiger; et al.
Abstract : Human mesenchymal stromal cells (MSC) possess immunosuppressive and antimicrobial effects that are partly mediated by the tryptophan-catabolizing enzyme indoleamine-2, 3-dioxygenase (IDO). Therefore MSC represent a promising novel cellular immunosuppressant which has the potential to control steroid-refractory acute graft versus host disease (GvHD). In addition, MSC are capable of reducing the risk of infection in patients after haematopoietic stem cell transplantation (HST). Recent data indicate that signals from the microenvironment including those from microbes may modulate MSC effector functions. As Cytomegalovirus (CMV) represents a prominent pathogen in immunocompromised hosts, especially in patients following HST, we investigated the impact of CMV infection on MSC-mediated effects on the immune system. We demonstrate that CMV-infected MSC lose their cytokine-induced immunosuppressive capacity and are no longer able to restrict microbial growth. IDO expression is substantially impaired following CMV infection of MSC and this interaction critically depends on intact virus and the number of MSC as well as the viral load. Since overt CMV infection may undermine the clinical efficacy of MSC in the treatment of GvHD in transplant patients, we recommend that patients scheduled for MSC therapy should undergo thorough evaluation for an active CMV infection and receive CMV-directed antiviral therapy prior to the administration of MSC.